An Application of Factor Analysis for Comparison of Morphological Characters of the Bamboo - Mahajan, P.K.; Awasthi, Nishant (Indian Journal of Agroforestry, 2020)
The technique of Factor Analysis has been applied to extract basic factors underlying the observed morphological characters of the bamboo (Dendrocalamus strictus, Roxb.). It was found that the three factors corresponding to (1) culm volume which explains 36.076 per cent of the total variation; (2) pulp yield factor which explains 24.344 per cent of the total variation and (3) the total yield factor which explains 14.47 per cent of the total variation have been brought out as the basic factors and can be used for comparison of important morphological characters of the bamboo.